2012
DOI: 10.1002/ece3.330
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutrient enrichment on the growth, nucleic acid concentrations, and elemental stoichiometry of coral reef macroalgae

Abstract: The growth rate hypothesis (GRH) links growth rates with organism elemental stoichiometry. Support for the GRH was found for many animal species, but less so for plants. This is the first study to test the GRH in macroalgae. Tropical coral reef macroalgae from three lineages, Caulerpa serrulata (Chlorophyta), Laurencia intricata (Rhodophyta), and Sargassum polyphyllum (Phaeophyceae) were grown enriched with nitrogen or phosphorous and under control conditions at Heron Island on the Great Barrier Reef, Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 74 publications
(122 reference statements)
4
21
1
1
Order By: Relevance
“…), we found no link between RNA:DNA and growth of Phyllospora from either origin. This decoupling supports the observations of Reef et al () who currently provide the only other study (to our knowledge) to investigate the applicability of the GRH to macroalgae. Although patterns of RNA:DNA ratios roughly followed net growth in NSW seaweed (i.e., highest at 17°C), there was no correlation between RNA:DNA ratios and growth at the level of individual thalli.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…), we found no link between RNA:DNA and growth of Phyllospora from either origin. This decoupling supports the observations of Reef et al () who currently provide the only other study (to our knowledge) to investigate the applicability of the GRH to macroalgae. Although patterns of RNA:DNA ratios roughly followed net growth in NSW seaweed (i.e., highest at 17°C), there was no correlation between RNA:DNA ratios and growth at the level of individual thalli.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the GRH is only predicted to apply if growth is nutrient‐limited. Reef and Lovelock () suggest that macroalgae may not conform to the GRH because of their considerable ability to store nutrients, and that RNA production may instead be associated with futile cycling such as photorespiration and ammonium cycling. Given that nitrate treatments were administered at concentrations within the ranges of those naturally experienced in a largely oligotrophic system, ammonium cycling is highly unlikely and photorespiration does not adequately explain the temperature regulation of RNA synthesis previously described.…”
Section: Discussionmentioning
confidence: 99%
“…). Although a strong relationship between P, RNA and growth rates has been observed over many taxa, we found positive but highly variable (non‐significant) relationships between %P and C:P and RNA:DNA, but stronger links to %N (and C:N and N:P), similar to that observed in experimental studies (Reef, Pandolfi & Lovelock ). A study of phytoplankton also found little evidence to support the Growth Rate Hypothesis (Flynn et al .…”
Section: Discussionsupporting
confidence: 87%
“…Another relevant factor that can influence the productivity of a seaweed crop is the availability, uptake, and assimilation of nutrients (Rees , Reef et al. ). It is well known that nutrient limitation has been associated with several negative impacts on seaweed ecophysiology (i.e., an increased vulnerability to photoinhibition by different radiations and slower growth; Dean and Jacobsen , Döhler et al.…”
mentioning
confidence: 99%